KARAKTERISTIK SOSIAL EKONOMI KEPALA RUMAH TANGGA DAN MUNCULNYA PEKERJA ANAK DI NTT 2022 - Heri Raharja; Endan Suwandana (Jurnal Statistika Terapan (ISSN 2807-6214), 2023)
Nusa Tenggara Timur (NTT) Province is not free from child labor phenomenon. Using March 2022 Sosio-Economic Survey (Susenas) and two research methods (descriptive & inferential), the research aims to obtain characteristics of head of household that significantly affect child labor in NTT. The result shows that there are 3,98% working children in NTT. Statistically, head of household mostly live in rural (85,3%), men (90,2%), minimum graduated from elementary school (74,6%), not working/work in the informal sector (78,6%), and has two or more economically dependent member in the household (80,5%). The result of binary logistic regression analysis shows that child labor has more risk to emerge when they live in a household headed by females, live in a rural, the head of household is uneducated/not graduated from elementary school, and the head of household is working in the informal sector/not work.